Illocutionary Speech Acts of Verbal Bullying in Dahl’s the Big Friendly Giant and Its Impacts on Self-Esteem of the Main Characters - Maisarah, Ira; Yayan, Yayan; Yunita, Wisma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The thesis aims to describe illocutionary speech acts of verbal bullying from a children’s literature entitled the Big Friendly Giant written by Roald Dahl. The research was designed as a qualitative study and applied content analysis. The used instruments were the tables contained illocutionary speech acts indicating verbal bullying and self-esteem. The data formed in the narrative quotations, which those were analyzed with applying Searle’s illocutionary speech acts. Verbal bullying were classified into six types, such as insulting, reviling, calling by bad name, public shaming, spreading gossip, and accusing. Furthermore, the data were connected with the issue of self-esteem having five senses proposed by Reasoners, such as sense of security, identity, belonging, purpose, and competence. The results indicated that two main figures experienced four of six verbal bullying types, such as insulting consisting of 19 utterances, or 73% of whole data, 1 datum of reviling (5.3%), 5 data of calling by bad names (19%), and 1 of accusing (5.3%). Meanwhile, the data of self-esteem informed 1 utterance of sense of identity (7%), belonging (2 utterances or 15%), purpose (5 utterances, 36%), and competence (6 utterances or 43%). In conclusion, the Big Friendly Giant can be recommended as English subject material because of providing a unique illustration for school students in dealing with verbal bullying which motivates them to erecttheir better future. KeyWords: Illocutionary Speech Acts, Self-Esteem, the Big Friendly Giant, Verbal Bullying.